Preinduction Cervical Ripening by Intrauterine Condom Balloon Method: A Preliminary Report - Hompoonsup, Boonroje; Seesod, Apai (Journal of Health Science of Thailand, 1994)
The authors report the preliminary results of clinical trial study during April 1st,1994 to August 31 st, 1994 at the delivery unit of Phrae hospital. Twenty-two women With pregnancies proceeding beyond 40 weeks gestation were conducted into the study. All of these women had no labor pain, cervical dilatation not exceed 1 ﬁngerbreadth and no cervical effacement.Initial Bishop score assessment of the cervices showed average score of 1 (mode). Intrauterine condom balloon (IUCB) was inserted to prepare for cervical ripening. Bishop score had changed to ripening state (> 6) in 90.9% of cases (20 out of 22). The IUCB had fell out in 16 out of 22 cases (72.7%); the mean time from insertion to fell out of IUCB were signiﬁcantly shorter in the parous compared to primiparous group (8 hours 35 minutes VS 17 hours 54 minutes p<0.01 accordingly) and Bishop score had reached 8 (mode) on average. The IUCB were removed after insertion for 24 hours in six cases and in this group average Bishop score were equal to 7 (mode). The mean induction to delivery interval were slightly shorter in the parous group than in the primiparous group (5 hours 5 minutes VS 6 hours 16 minutes). However there were no statistically signiﬁcant differences (p>0.05), One and ﬁve minutes-Apgar score of the babies born from these women were in the normal range No harmful side effects to the mothers and her child from this procedure were noted during the study periods.